Aspirate from human stented saphenous vein grafts induces epicardial coronary vasoconstriction and impairs perfusion and left ventricular function in rat bioassay hearts with pharmacologically induced endothelial dysfunction. Issue 15 (1st August 2016) - Lieder, Helmut R.; Baars, Theodor; Kahlert, Philipp; Kleinbongard, Petra
Abstract: Stent implantation into aortocoronary saphenous vein grafts (SVG) releases particulate debris and soluble vasoactive mediators, for example, serotonin. We now analyzed effects of the soluble mediators released into the coronary arterial blood during stent implantation on vasomotion of isolated rat epicardial coronary artery segments and on coronary flow and left ventricular developed pressure in isolated perfused rat hearts. Coronary blood was retrieved during percutaneous SVG intervention using a distal occlusion/aspiration protection device in nine symptomatic patients with stable angina pectoris and a flow‐limiting SVG stenosis. The blood was separated into particulate debris and plasma. Responses to coronary plasma were determined in isolated rat epicardial coronary arteries and in isolated, constant pressure‐perfused rat hearts (±nitric oxide synthase [NOS] inhibition and ±serotonin receptor blockade, respectively). Coronary aspirate plasma taken after stent implantation induced a stronger vasoconstriction of rat epicardial coronary arteries (52 ± 8% of maximal potassium chloride induced vasoconstriction [% KClmax = 100%]) than plasma taken before stent implantation (12 ± 8% of KClmax ); NOS inhibition augmented this vasoconstrictor response (to 110 ± 15% and 24 ± 9% of KClmax ). Coronary aspirate plasma taken after stent implantation reduced in isolated perfused rat hearts only under NOS inhibition coronary flow by 17 ± 3% and left ventricular developed pressure by 25 ± 4%. Blockade of serotonin receptors abrogated these effects. Coronary aspirate plasma taken after stent implantation induces vasoconstriction in isolated rat epicardial coronary arteries and reduces coronary flow and left ventricular developed pressure in isolated perfused rat hearts with pharmacologically induced endothelial dysfunction. Abstract : Human coronary arterial aspirate, retrieved after stent implantation during percutaneous coronary intervention, induces vasoconstriction in isolated epicardial rat coronary arteries and impairs coronary flow and left ventricular function in isolated perfused rat hearts with pharmacologically induced endothelial dysfunction.